ANALISIS PENGARUH NILAI TUKAR RUPIAH, FOREIGN DIRECT INVESTMENT (FDI), DOMESTIC DIRECT INVESTMENT ( DDI) DAN TINGKAT INFLASI TERHADAP EKSPOR INDUSTRI KREATIF INDONESIA PADA TAHUN 2011-2015 - Joddy Herlambang; Nur Barokah; Endang Sulistyani (JOBS (Jurnal Of Business Studies), 2016)
This study is intended to find out that rupiah exchange rates, foreign direct investment, domestic direct investment and inflation rates, have an effect toward the value of export of creatie industries. The analysis techniques used in this study is the technique of multiple linear regression analysis with Ordinary Least Square (OLS) method, F-test for simultaneously testing and t-test for partial testing. Results of data analysis showed simultaneously the rupiah exchange rates, the foreign direct investment, the domestic direct investment and the inflation rates that had significant effect on the export of creatie industries. F-test results show that the value of Prob (Fstatistic) is 0.00000 < default values of significance (0.05) with a coefficient of determination (R2) of 0.984487, which means that the variable rupiah exchange rates, foreign direct investment, domestic direct investment and inflation rates contribution amounting to 98,4 % .The remaining 1,6 % was explained by other variables. Partially, the independent variables rupiah exchange rates and domestic direct investment have positive and significant impact on export of creatvie industries. Meanwhile the other independent variables foreign direct investment and inflation rates have negative and significant impact on export of creative industries.